Individual differences as predictors of dietary patterns among menopausal women with arterial hypertension - Gacek, Maria (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction: The aim of this study was to analyze selected individual determinants of dietary choices, important for etiology and prevention of degenerative cardiovascular disorders, in a group of menopausal women diagnosed with arterial hypertension. Material and methods: The study included a group of 160 women from the Małopolska region, aged between 45 and 60 years and diagnosed with arterial hypertension. A questionnaire assessing the frequency of food product consumption was used, along with standardized psychological tests (GSES, LOT-R, and SWLS). Spearman’s coefficients of rank correlation and the Kruskal-Wallis and Dunn tests were used for statistical analysis. Results: We revealed that higher levels of self-efficacy were associated with more frequent consumption of whole grains, oatmeal, raw vegetables, fruit, semi-skimmed milk, natural yoghurt, marine fish, legume seeds, soy products, nuts, plant oils, and fruit and vegetable juices, as well as with less frequent consumption of whole milk, high-fat cottage cheese, and sweetened carbonated beverages and alcoholic beverages. The levels of optimism and satisfaction with life correlated positively with the consumption frequency of brown rice, whole grains, oatmeal, fruit, marine fish, legumes, soy products, nuts, butter, and fruit juices, and were inversely correlated with the consumption of white bread, high-fat cottage cheese, pork meat and sausages, and sweets and pastries. Conclusions : Postmenopausal women with arterial hypertension who were characterized by lower levels of self-efficacy, optimism, and satisfaction with life made less rational dietary choices which could negatively affect the efficacy of the secondary prevention of cardiovascular degenerative disorders.